OVERVIEW OF HPV(human papillomavirus) VACCINE ACCEPTANCE IN STUDENTS - Desty, Rani Tiara; Subarti, Dwi (MEDFARM: Jurnal Farmasi dan Kesehatan, 2025)
Cervical cancer is the third most common cancer among women worldwide, with more than 75% of cases occurring in developing countries. Cervical cancer is the second most common cancer case in Indonesia. The government is preparing a strategy to prevent cervical cancer with HPV vaccination, one of which is for unmarried teenagers. This is supported by the fact that intercourse is now becoming more free and many people are having sexual relations in the 17 to 21 year age group. Many teenagers are afraid to get the HPV vaccination. Wrong beliefs can influence the acceptance of cervical cancer management and prevention. This study was aims to determine the acceptance of HPV vaccination as an early prevention of cervical cancer in pharmacy students. The type of research that will be carried out is quantitative descriptive research with a cross-sectional approach. The population in this study were all Pharmacy Students Class of 2024. The sample taken in this study was a total sampling with a total of 142 students. The variable studied was student acceptance of HPV vaccination. The instrument used was a questionnaire with Google Form. Data analysis using univariate. The results of research on acceptance of the HPV vaccine among students show that the majority of respondents were female (93.7%). More than half (54.9%) of respondents were 18 years old. More than half, 55.6% of respondents, were less able to receive the HPV vaccine. Education among teenagers, especially students, regarding HPV vaccination needs to be improved, so that they can understand and accept HPV vaccination and as prospective health workers can become role models for changing health behavior Keywords: Students, Receiving, HPV Vaccine.